2017
DOI: 10.5435/jaaos-d-16-00103
|View full text |Cite
|
Sign up to set email alerts
|

Septic Arthritis of the Shoulder: A Comparison of Treatment Methods

Abstract: Therapeutic level III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 14 publications
1
18
0
Order By: Relevance
“…[16][17][18][19] The percentage of patients afflicted by septicemia and septic shock were also reported in Jiang et al's study at 24.2% and 2.3%, respectively. 16 Hematogenous spread from bacteremia is the most common cause of septic arthritis representing roughly 70% of cases, and bacteremia is more likely to affect a large joint with pre-existing arthritis. 2 Therefore, the patient's underlying osteoarthritis put him at higher risk for hematogenous seeding of this joint.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…[16][17][18][19] The percentage of patients afflicted by septicemia and septic shock were also reported in Jiang et al's study at 24.2% and 2.3%, respectively. 16 Hematogenous spread from bacteremia is the most common cause of septic arthritis representing roughly 70% of cases, and bacteremia is more likely to affect a large joint with pre-existing arthritis. 2 Therefore, the patient's underlying osteoarthritis put him at higher risk for hematogenous seeding of this joint.…”
Section: Discussionsupporting
confidence: 67%
“…Septic arthritis of the shoulder accounts for 5%-12% of all cases of septic arthritis with the overall incidence being 3200 cases per year in the USA. [14][15][16] Jiang et al reviewed 7145 cases of native shoulder septic arthritis in the USA, finding that the overall inpatient mortality rate was 2.6% for these patients, while other studies have reported mortality rates as high as 11%-17%. [16][17][18][19] The percentage of patients afflicted by septicemia and septic shock were also reported in Jiang et al's study at 24.2% and 2.3%, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is possible that shoulder SA may be under‐evaluated and under‐diagnosed. The most common cause of septicemia as a complication of shoulder SA has been attributed to MSSA 20,22 . To our knowledge, our study is the first to find MRSA as the most common pathogen causing shoulder SA.…”
Section: Discussionmentioning
confidence: 55%
“…However, Bovonratwet et al [ 18 ] reported similar rates of reoperation and postoperative complications between the two surgical methods. Jiang et al [ 19 ] also reported no difference in the reoperation rate between these two surgical methods. Some studies showed that arthroscopic surgery is ineffective on higher Gächter stages of septic arthritis [ 9 , 20 ].…”
Section: Discussionmentioning
confidence: 99%